The role of social exclusion and gender in the relationship between family life satisfaction and game addiction among adolescents - Ibrahim Taş (BMC Psychology)
Abstract Background This study investigates the relationship between family life satisfaction and game addiction, with a focus on the moderating role of social exclusion and gender, and the mediating effect of social exclusion. The main objectives were to investigate (1) whether social exclusion moderates the relationship between family life satisfaction and game addiction, (2) whether family life satisfaction affects game addiction indirectly through social exclusion, and (3) whether gender moderates the indirect effect of family life satisfaction on game addiction via social exclusion. Methods Data were collected from 423 adolescents (56.7% female, 43.3% male) aged 14–18. Participants completed the Family Life Satisfaction Scale, the Game Addiction Scale for Adolescents, and the Ostracism Experience Scale. Moderation, mediation, and conditional process analyses were conducted using the PROCESS macro in SPSS. Results Social exclusion significantly moderated the relationship between family life satisfaction and game addiction. Adolescents with lower family life satisfaction and higher levels of social exclusion exhibited greater game addiction. Social exclusion also partially mediated the relationship between family life satisfaction and game addiction. Gender moderated the indirect effect of family life satisfaction on game addiction through social exclusion. Conclusion These results highlight the critical roles of family dynamics, social exclusion, and gender in understanding game addiction among adolescents.